Stability of differential equations with piecewise constant argument via discrete equations - Marconato, Suzinei A.S. [UNESP]; Spezamiglio, Adalberto [UNESP] (My University, 2000)
Lyapunov stability for a class of differential equation with piecewise constant argument (EPCA) is considered by means of the stability of a discrete equation. Applications to some nonlinear autonomous equations are given improving some linear known cases.